FRAMING THE GRID: MEDIA NARRATIVE, PUBLIC DISCOURSE, AND THE POLITICS OF ENERGY PRICING - DR. FAIZA BAJWA , DR ASIA SAIF ALVI , OMER FAROOQ DOGAR , HAFIZ MUHAMMAD UMAR , DR TARIQ USMAN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This study examines the critical interplay between media framing, public perception, and political decision-making in energy pricing debates. Employing a mixed-methods approach—including content analysis of traditional and digital media, social media analytics, and public perception surveys—the research investigates how narrative construction influences policy legitimacy and reform feasibility. Focusing on Pakistan as a primary case and integrating comparative insights, the analysis reveals a fragmented media landscape where linguistic, ideological, and platform-based divisions produce competing narratives around affordability, sovereignty, reliability, and sustainability. These narratives significantly affect public willingness to pay, institutional trust, and protest mobilization. The study contributes to energy transition literature by highlighting the discursive and political dimensions of pricing reforms in developing economies and offers evidence-based recommendations for strategic communication and participatory policymaking.